2022
DOI: 10.1039/d2qi01238c
|View full text |Cite
|
Sign up to set email alerts
|

An efficient vanadium/cobalt metaphosphate electrocatalyst for hydrogen and oxygen evolution in alkaline water splitting

Abstract: Hydrogen, which meets the goal of carbon neutrality, is expected to replace conventional fossil fuels in the near future. Electrochemical water splitting is a clean hydrogen production technology, but its...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…It was also pointed out that the strong interaction between Ni(OH) 2 and ACC hindered the reduction of Ni 2+ to Ni 2 P. As a result, metaphosphate rather than phosphide was obtained during phosphating progress. When the precursor is changed to Co 5 (O 9.48 H 8.52 )NO 3 75 or even a piece of nickel foam (NF) immersed in a mixed solution of Co(NO 3 ) 2 ·6H 2 O and VCl 3 , 76 they can also be converted into the corresponding metaphosphates successfully using the gas‐phase phosphorylation method. Furthermore, the metaphosphate material of the composite structure can also be constructed in the same way.…”
Section: Synthetic Strategies Of Tmmpsmentioning
confidence: 99%
“…It was also pointed out that the strong interaction between Ni(OH) 2 and ACC hindered the reduction of Ni 2+ to Ni 2 P. As a result, metaphosphate rather than phosphide was obtained during phosphating progress. When the precursor is changed to Co 5 (O 9.48 H 8.52 )NO 3 75 or even a piece of nickel foam (NF) immersed in a mixed solution of Co(NO 3 ) 2 ·6H 2 O and VCl 3 , 76 they can also be converted into the corresponding metaphosphates successfully using the gas‐phase phosphorylation method. Furthermore, the metaphosphate material of the composite structure can also be constructed in the same way.…”
Section: Synthetic Strategies Of Tmmpsmentioning
confidence: 99%
“…Among the above-mentioned catalysts, transition metal metaphosphates (TMMPs) with abundant MO x and PO 4 units have received growing interest since the Fe­(PO 3 ) 3 -Ni 2 P catalysts were reported with extremely high OER activity (177 mV at 10 mA cm –2 ) and stability . Afterward, it is found that doping TMMPs with anions or cations can further improve their OER performance. For example, our group has designed a series of bimetallic metaphosphate nanoarrays for catalyzing the OER, among which the CoNiP 4 O 12 with optimized Ni dopants was demonstrated to balance the doping effect and morphology effect, presenting outstanding OER performance.…”
Section: Introductionmentioning
confidence: 99%
“…With an ever-increasing development of green and sustainable energy technologies, hydrogen energy has long been considered the most promising alternative to traditional fossil fuels. In this context, the efficient electrochemical hydrogen evolution reaction (HER) driven by water electrolysis has been extensively studied. Despite platinum–carbon (Pt/C) exhibiting compelling HER activity and selectivity, its expensive price and limited reserve severely hinder the wide range of practical applications. , Meanwhile, it is well-known that these commercial 20% Pt/C catalysts are usually faced with the problem of low atomic utilization and moderate catalytic stability as a result of excessive metal particle accumulation owing to high platinum content. Therefore, how to improve the atom efficiency and long-term stability of catalytic materials remains to be resolved for a more green and harmonious society …”
mentioning
confidence: 99%